Exact bounds for steepest descent algorithms of L-convex function minimization - Murota, Kazuo; Shioura, Akiyoshi (Operations research letters, 2014)
We analyze minimization algorithms for L♮-convex functions in discrete convex analysis and establish exact bounds for the number of iterations required by the steepest descent algorithm and its variants.